SKULL MORPHOMETRY OF THE BOTI MONKEY - Yuniq Insanillahia,; I Gede Soma,; I Made Sukada, (Buletin Veteriner Udayana, 2024)
Boti monkey or Macaca tonkeana is one of the endemic animals from Central Sulawesi whose conservation status is categorized as Vulnerable. Skull morphometry measurements are needed especially for Sulawesi endemic primates, this is because skull morphometry studies can have implications in conservation issues, helping to identify populations that may require special attention or conservation measures. The purpose of this study was to determine the size dimensions of the boti monkey skull. This study used two boti monkey skulls that were measured with linear measurements using a digital caliper. Data collection of skull volume is done by entering the skull into a measuring container filled with water. The results showed the average bimaxillary width 43.02 mm, skull length 142.56 mm, bizygomatic width 91.13 mm, biauricular width 73.57 mm, cranial width 66.99 mm, basalskull length 97.25 mm, nasion-basion length 67.47 mm, basibregmatic height 49.47 mm, maxillar tooth row length 50.49 mm, mandible length 96.77 mm, bicondilar width of mandible 74.41 mm, biorbital width 69, 07 mm, bimalar width 83.54 mm, orbits width 54.03 mm, postorbital width 45.43 mm, supramaxillary width 28.15 mm, bicanine width 35.77 mm, incisor width 20.88 mm, bimolar width 39.06 mm, maxillary molar tooth row 23.45 mm, facial height 40.12 mm, postrostral length 85.91 mm, rostral length 64.63 mm, facial length 47.62 mm, and skull volume I 100 ml and skull II 50 ml. It can be concluded that there is a size difference between skull I and skull II. It is necessary to conduct further research on the volume of the boti monkey skull using more accurate measuring instruments and conduct DNA tests to determine the sex of the skull.